Social resilience within the carescapes of Asian female migrant aged care workers - Winarnita, Monika; Leone, Carmela; Klassen, Thomas; Blackberry, Irene D. (Frontiers in Public Health, 2025)
Increasingly, Asian female migrants are playing a significant role in meeting Australia’s aged care workforce demand. This article analyses the lived experiences of Asian female aged care workers using the carescape concept, and a theory of agency to understand aged care access and workforce availability. It aims to identify the wider institutional and social structures that influence their agency and contribute to their social resilience as a critical member of the aged care workforce. Qualitative data were used for analysis; specifically, semi-structured interviews which were conducted with 10 Asian female migrant workers from the aged care sector. Analysis reveals that social and institutional structures both challenge and facilitate agency, and thus access to the aged care industry. The findings provide a deeper understanding of agency and highlights the social structures which contribute to developing social support networks and social resilience. Workplace policies and practices which facilitate the agency, adaptation and transformation of this workforce are important to understanding access to the industry and the retention of Asian female migrant aged care workers.